2020
DOI: 10.3847/1538-4357/abb77b
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA Survey of the SCUBA-2 Cosmology Legacy Survey UKIDSS/UDS Field: The Far-infrared/Radio Correlation for High-redshift Dusty Star-forming Galaxies

Abstract: We study the radio properties of 706 submillimeter galaxies (SMGs) selected at 870 μm with the Atacama Large Millimeter Array from the SCUBA-2 Cosmology Legacy Survey map of the Ultra Deep Survey field. We detect 273 SMGs at >4σ in deep Karl G. Jansky Very Large Array 1.4 GHz observations, of which a subset of 45 SMGs are additionally detected in 610 MHz Giant Metre-Wave Radio Telescope imaging. We quantify the far-infrared/ radio correlation (FIRRC) through parameter q IR , defined as the logarithmic ratio of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 127 publications
6
41
2
Order By: Relevance
“…Accounting for the frequency difference through scaling with α=−0.70, our S-band observations are a factor ∼13 deeper than these lower-frequency data, and hence the 1.4 GHz observations are mostly useful for the brightest sources detected at 3 and 10 GHz. Additionally, a sevenpointing mosaic at 34 GHz (rms∼1.4 μJy beam −1 , area ∼10 arcmin 2 ) exists as part of the COLDz project (Pavesi et al 2018;Riechers et al 2019;Algera et al 2020). The COSMOS-XS 10 GHz data is directly centered on this mosaic, allowing for a detailed analysis of the long-wavelength spectrum of faint radio sources with up to four frequencies.…”
Section: Radio Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for the frequency difference through scaling with α=−0.70, our S-band observations are a factor ∼13 deeper than these lower-frequency data, and hence the 1.4 GHz observations are mostly useful for the brightest sources detected at 3 and 10 GHz. Additionally, a sevenpointing mosaic at 34 GHz (rms∼1.4 μJy beam −1 , area ∼10 arcmin 2 ) exists as part of the COLDz project (Pavesi et al 2018;Riechers et al 2019;Algera et al 2020). The COSMOS-XS 10 GHz data is directly centered on this mosaic, allowing for a detailed analysis of the long-wavelength spectrum of faint radio sources with up to four frequencies.…”
Section: Radio Datamentioning
confidence: 99%
“…However, galaxies that host an AGN may have their radio emission dominated instead by the active nucleus, and will therefore be offset from the FIRC. To quantify this, we define the correlation parameter q TIR as the logarithmic ratio of a galaxy's total-IR luminosity L TIR , measured between (restframe) 8-1000 μm, and its monochromatic radio luminosity at rest-frame 1.4 GHz, L 1.4GHz (following e.g., Bell 2003;Thomson et al 2014;Magnelli et al 2015;Delhaize et al 2017;Calistro Rivera et al 2017;Algera et al 2020…”
Section: Radio-excess Agnsmentioning
confidence: 99%
“…For example, the total flux density and, hence, the size of moderately resolved sources can differ between radio maps with different spatial resolutions (Murphy et al 2017;Bondi et al 2018). 13 We note that adopting a redshift-dependent IR-radio correlation (e.g., Delhaize et al 2017;Algera et al 2020) does not affect the sense (or significance) of the trends reported in this work.…”
Section: Estimating the Radio Size Of Galaxiesmentioning
confidence: 78%
“…One dust-unbiased, but indirect, probe of star formation can be obtained by mapping the predominantly nonthermal radio continuum emission of galaxies at centimeter wavelengths (e.g., Condon 1992;Bell 2003;Garn et al 2009;Murphy et al 2011). This star formation rate (SFR) indicator has been calibrated using the tight, yet empirical, far-infrared (far-IR)radio correlation (Helou et al 1985;Yun et al 2001;Murphy et al 2006aMurphy et al , 2006bMurphy et al , 2012bMurphy 2009;Sargent et al 2010;Magnelli et al 2015;Delhaize et al 2017;Gim et al 2019;Algera et al 2020). The physical interpretation of this relation is that far-IR emission arises from the absorption and reradiation of UV and optical photons that heat dust grains surrounding massive star-forming regions.…”
Section: Introductionmentioning
confidence: 99%
“…This exists in star-forming galaxies because radio emission is intimately correlated with the FIR due to their mutual origin in active high-mass star-forming regions. This correlation is found to hold at high redshifts (Yun et al 2001;Garrett 2002;Sargent et al 2010; Thomson et al 2014;Pannella et al 2015;Magnelli et al 2015;Delhaize et al 2017;Algera et al 2020a), thus any AGN activity can be identified by deviations from this correlation. Here the AGN produces the excess radio emission (e.g., Donley et al 2005;Del Moro et al 2013).…”
Section: Introductionmentioning
confidence: 90%